Kakas Bantu untuk Penentuan Prioritas Test Scenario Berdasarkan UML Activity Diagram - Fatimatuz Zahro; Fajar Pradana; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In software development there are stages of testing that have a very important role. Testing ensures that in the system there are no bugs and errors. Continuous software changes make it impossible to carry out the overall test. However, changes that occur in the environment, platform, etc., must be re-tested as a whole. To overcome the overall testing will be time consuming, expensive, inefficient and ineffective. So that to overcome the overall test requires regression testing with model-based prioritization test case strategies. To deal with this problem, a manual calculation of the test scenario is carried out with a prioritization test case strategy with weighting factors in the UML activity diagram model. Manual calculations have disadvantages such as requiring a lot of time, human resources, and so on. Therefore an auxiliary a tool is made for the calculation of test scenario priority based on the UML activity diagram. This system was built with C # technology and tested using the white-box testing method on unit testing as well as the black-box testing method in validation testing. On unit testing and validation testing, the test results are 100% valid.